2020
DOI: 10.1111/ppl.13184
|View full text |Cite
|
Sign up to set email alerts
|

IRONing out stress problems in crops: a homeostatic perspective

Abstract: Iron (Fe) is essential for plant growth and therefore plays a key role in influencing crop productivity worldwide. Apart from its central role in chlorophyll biosynthesis and oxidative phosphorylation (electron transfer), it is an important constituent of many enzymes involved in primary metabolism. Fe has different accessibilities to the roots in the rhizosphere depending upon whether it is ferrous (soluble) or ferric (insoluble) oxidation stages, which in turn, determine two kinds of Fe uptake strategies emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 168 publications
1
4
0
Order By: Relevance
“…Although a previous study reported more severe phenotypes under longer Fe deprivation (Erenoglu et al, 2000), results of this current study demonstrate that just five days were sufficient to elicit clear deficiency symptoms in barley leaves. This aligns with research indicating a direct correlation between treatment duration and chlorosis severity in Fe-sensitive cultivars (Bandyopadhyay & Prasad, 2021;Martín-Barranco et al, 2021). Thus, Tarm-92 emerges as highly sensitive to Fe deficiency, exhibiting significant impairments even after a shortterm deprivation.…”
Section: Barley Roots and Shoots Are Adversely Affected By Fe Deficiencysupporting
confidence: 88%
See 1 more Smart Citation
“…Although a previous study reported more severe phenotypes under longer Fe deprivation (Erenoglu et al, 2000), results of this current study demonstrate that just five days were sufficient to elicit clear deficiency symptoms in barley leaves. This aligns with research indicating a direct correlation between treatment duration and chlorosis severity in Fe-sensitive cultivars (Bandyopadhyay & Prasad, 2021;Martín-Barranco et al, 2021). Thus, Tarm-92 emerges as highly sensitive to Fe deficiency, exhibiting significant impairments even after a shortterm deprivation.…”
Section: Barley Roots and Shoots Are Adversely Affected By Fe Deficiencysupporting
confidence: 88%
“…DMA is converted to mugineic acid (MA) by IRON DEFICIENCY SPECIFIC CLONE3 (IDS3), which functions as a dioxygenase in barley roots (Kobayashi et al, 2001). Nine MAs have been identified so far in rye and barley (Bandyopadhyay & Prasad, 2021). They are released from plant roots to the rhizosphere as PS via TRANSPORTER OF MA1 (TOM1) (Nozoye et al, 2011), forming a complex with insoluble Fe 3+ in the soil, and then they are taken up into the root epidermis by specific oligopeptide transporters such as YELLOW STRIPE1 (YS1) in Zea mays and YELLOW STRIPE-LIKE15 (YSL15) in Oryza sativa (Aksoy et al, 2018;Rai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Stress-induced DELLA accumulation reduced the bioactive GA content by inhibiting the expression level of GA3ox , increased the activities of reactive oxygen species (ROS) detoxification enzymes (catalases and Cu/Zn-superoxide dismutases) and reduced the ROS accumulation in plants [ 53 , 54 ]. In addition, previous studies reported that iron-containing enzymes (superoxide dismutase, catalase, and glutathione peroxidase) were involved in the detoxification of ROS [ 55 , 56 ], and iron deficiency is believed to be dependent on the type and quantity of mugineic acid [ 57 ]. A functional annotation showed that the orthologous genes of Cs2ODD-C36 in O. sativa was IDS3 (Os07g07410) encoding 2′-deoxymugineic-acid 2′-dioxygenase, which was involved in the formation of mugineic acids [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an essential nutrient for plants and animals; 1 however, crop species struggle for Fe nutrition, the reason being the low Fe availability for plants. 2 Fe bioavailability is strongly dependent on chemical reactions with soil components. 3 Alternatively, Co has been described as a beneficial element, which means that low concentrations (0.01 to 10 mg kg −1 ) stimulate plant growth and yield, improve drought, salt, and heavy metal resistance, inhibit ethylene biosynthesis, and promote nitrogen fixation by increasing the number of nodules in legumes.…”
Section: Introductionmentioning
confidence: 99%